2020
DOI: 10.3390/ijerph17165862
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Nanomaterials as Promising Material for Wastewater Treatment Processes

Abstract: In the latest literature search, the technology based on graphite oxide (GO) nanomaterials exhibits a great potential in many aspects of wastewater treatment involving adsorption, photocatalysis, disinfection and membrane process. In this study experimental data involving the carbon element in different forms such as active carbon (AC), graphite and graphene oxide (GO) applied as the active reagents in wastewater treatment are summarized and discussed. The first step was to characterize the aforementioned carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Results of multivariate calculations clearly suggested differences in bisphenols behavior in the presence of β-cyclodextrin or β-cyclodextrin/duckweed additives. In our latest work based on activated sludge jar test we confirmed the complex interaction of graphene oxide (GO) nanoparticles with microorganisms that are present in activated sludge working with real wastewater [ 6 ]. Univariate measurements including pH, conductivity, TOC, IC, ammonia, and total nitrogen together with multivariate statistics calculations (principal component analysis) clearly revealed that GO may significantly affect the wastewater technological processes investigated.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Results of multivariate calculations clearly suggested differences in bisphenols behavior in the presence of β-cyclodextrin or β-cyclodextrin/duckweed additives. In our latest work based on activated sludge jar test we confirmed the complex interaction of graphene oxide (GO) nanoparticles with microorganisms that are present in activated sludge working with real wastewater [ 6 ]. Univariate measurements including pH, conductivity, TOC, IC, ammonia, and total nitrogen together with multivariate statistics calculations (principal component analysis) clearly revealed that GO may significantly affect the wastewater technological processes investigated.…”
Section: Resultsmentioning
confidence: 90%
“…In our previous works we demonstrated degradation of different endocrine disrupting compounds (EDCs), using protocols involving aerobic batch experiment with activated sludge obtained from the municipal sewage treatment plant [ 20 ] as well as duckweed biomass [ 21 ]. Moreover, we investigated behavior of activated sludge biomass in the presence of different type of carbon materials including graphene oxide nanoparticles [ 6 ]. Our experimental work using Ternes methodology [ 22 , 23 ] demonstrated relatively fast degradation rate of different steroids including estriol and testosterone, whilst equilin was fairly resistant for biodegradation under activated sludge aerobic conditions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene is formed out of flat monolayer of carbon atoms which are densely packed in a honeycomb lattice in 2-dimensions. The carbon atoms are sp 2 hybridized; hence, they form strong intra layer bonding within the hexagonal carbon-rings, which makes graphene one of the strongest materials to be prepared [21]. This results in carbon materials finding a myriad of applications where developments have led to the discovery of a multitude of uses of carbon.…”
Section: Short Summary Of the Development Of Advanced Carbon Materials Synthesis Methods And Applicationsmentioning
confidence: 99%
“…From Figure 4 it is evident that the nanocomposite exhibited excellent adsorption and photodegradation in the first cycle of wastewater treatment although, the performance was slightly reduced in subsequent cycles, the performance still showed promising results for future use, which suggests that magnetic ZnFe2O4-graphene nanocomposites have potential as an alternative to existing water purification processes. The understanding of low-dimension carbon material family (CNTs, fullerenes, graphenes, and QCDs) arrived, and indicated extensively remarkable properties for various applications [21].…”
Section: Microwave-assisted Synthesis For Advanced Carbon Materials In Energy and Sensingmentioning
confidence: 99%